Senior Driver Performance on Airport Road Access Wayfinding Design - Nur Khairiel Anuar; Rohafiz Sabar; Mazli Mutazam (International Journal of Supply Chain Management, 2019)
The purpose of this study was to evaluate the wayfinding and signage provisions, sensitivity of senior driving behavior and road safety. A driving simulator to simplify the airport navigation was developed. Three scenario types were designed to provide a variety of driving situations and complexity of the road designs to the airport. The complexity of way finding with the assorted road furniture such as signage adverts and street lights also were included. Experience car drivers who held valid UK driving license were asked to drive simulated routes. Fifteen drivers in range of age 50-54, 55-59 and over 60 years were selected to perform the study. Participants drove for approximately 20 minutes to complete the simulated driving. The types of errors (parameter) of simulated driving were identified: risk of collisions, exceed the speed limit, traffic light tickets, centerline crossings and road edge excursions. The drivers’ performance and parameter were compared to the age group. Results were analyzed by ANOVA and discussed with reference to the use of driving simulator. The ANOVA confirmed that senior drivers’ age group have no significant effect on the airport road design, wayfinding and all research parameters; risk of collisions, exceed the speed limit, traffic light tickets, centerline crossings and road edge excursions.